Extraction of valuable phytocompounds from medicinal plants of Clinacanthus Nutants Lindau by solvent-free microwave technique: article - Zulkefli, Ahmad Syaniz Syafiq; Mustapha, Ana Najwa (2019)
Clinacanthus Nutants Lindau(C.nutants) belonging to the Acanthaceae family also known as Sabah Snake Grass, mostly found in South East region. The solvents used for this research was distilled water. Process parameter was pursuing out under three different type power (160 W, 240 W and 360 W) and three different solvent-to-feed ratio which is (1:10, 1:20 and 1:30). These three ratios acted differently as the time needed is different between ratio 1:10, 1:20 and 1:30. The increase of solvent requires longer time for the heat to be supplied to the samples. Oher than that, the data shown that the extraction yield increase with as the power of the microwave increase. The highest yield observed was 28.91% (Power =360 W, S/F=1:30).